(untitled) (Proceedings of the International Conference on Education, 2020)
Collective memory of the Ambon Maluku community towards the conflict occurred in 1999-2003 that has awakened the value of pela gandong local wisdom owned for hundreds of years is very important to maintain. The function is also optimized to maintain the reconciliation of the Ambon Maluku conflict that has been achieved. The Ambon Maluku community defines pela gandong as the friendship model, fraternity system, or alliance system that was developed among all indigenous people from two or more countries even before the colonial arrived. When the Ambon conflict occurred, pela gandong became part of the conflict resolution. At present, the Ambon Maluku community has expanded the function of pela gandong to various fields including education. This study aimed to reveal the implementation of the value of pela gandong local wisdom in education and becoming a model of multicultural education in Maluku. This study was conducted in January 2018 at SMPN 9 Ambon with 99% of Christian/Catholic students and SMPN 4 Salahutu Liang with 100% of Moslem students. The research method used was descriptive qualitative to obtain the answers of the research. The data collecting techniques were literature study, interview, and participatory observation. The results of the research showed that the implementation of the values of pela gandong was relevant and could be integrated as a model of multicultural education.